PENGARUH KOMPETENSI PEDAGOGIK GURU DALAM MELAKSANAKAN PENILAIAN OTENTIK TERHADAP HASIL BELAJAR IPS PADA KURIKULUM 2013 DI SMPN KOTA BANDUNG DAN SMPN KOTA CIMAHI - Fiestawa, Riefki (2017)
Results of teaching and learning in kurukulum 2013 IPS, referring to the achievement of core competencies which be divided into four sections mutually sustainable, that is spiritual, social, knowledge and skills. To achieve these competencies, efforts to do is to carry out the assessment. Curriculum assessment standards in 2013 more emphasis on authentic assessment. Authentic assessment provides an opportunity for learners to construct learning results. Authentic assessment carried out during the learning process from the beginning until the end of the lesson learning. So that facilitating teachers to carry out an assessment of spiritual, social, knowledge, and skills. Because of necessary to carry out an authentic assessment of teacher competence in integrating learning with authentic assessment. This study reviewing the overview pedagogical competence of teachers in the use of authentic assessment and learning outcomes of students in social studies learning and see how the influence of pedagogical competence of teachers in implementing authentic assessment of the learning outcomes of students in social studies learning. The results show pedagogical competence of teachers in implementing authentic assessment related and positive influence on the study of students in social studies learning. This is supported by the results of descriptive statistical analysis, statistical test of Rank Spearman hypothesis, and test the coefficient of determination. In more detail this research described learning implementation planning, implementation of learning and implementation of learning authenic assessment conducted by educators to be high quality. While most of learning outcomes achieved with the implementation of authentic assessment is the spiritual competence.;--- Hasil belajar pembelajaran IPS di kurukulum 2013, mengacu pada capaian kompetensi inti yangdibagi kedalam empat bagian yang saling berkesinambungan, yakni spiritual, sosial, pengetahuan dan keterampilan.Demi tercapainya kompetensi tersebut, usaha yang dapat dilakukan adalah dengan melaksanakan penilaian. Standar penilaian di kurikulum 2013 lebih menekankan pada penilaian autentik. Penilain autentik memberikan kesempatan kepada peserta didik untuk mengkonstruksi hasil belajarnya. Penilaian autentik dilakukan selama proses pembelajaran mulai dari awal pembelajaran hingga akhir pembelajaran. Sehingga memfasilitasi guru untuk melaksanakan penilaian spiritual, sosial, pengetahuan, dan keterampilan. Oleh karena itu untuk melaksanakan penialaian autentik diperlukan komptensi guru dalam mengintegrasikan pembelajaran dengan penilaian autentik. Penelitian ini mengkaji gambaran kompetensi pedagogik guru dalam penggunaan penilaian autentik dan hasil belajar peserta didik padapembelajaran IPS serta melihat pengaruhpengaruhkompetensi pedagogik guru dalam melaksanakan penilaian autentik terhadaphasilbelajarpesertadidikpadapembelajaran IPS. Hasilnya menunjukkankompetensi pedagogik guru dalam melaksanakan penilaian autentik berhubungan dan berpengaruh positif terhadap hasil belajar peserta didik pada pembelajaran IPS.Ini didukung hasil analisis statistik deskriptif, uji statistik hipotesis Rank Spearman, dan uji koefisien determinasi.Secara lebih rinci digambarkan penilitianiniperencanaanpelaksanaanpembelajaran, pelaksanaanpembelajarandanpelaksanaanpenilaianautenik yang dilakukanolehpendidikmemilikikualitas yang tinggi. Sedangkan hasil belajar yang paling tercapai dengan pelaksnaan penilaian autentik adalah kompetensi spiritual.